Multilevel brain functional connectivity and task-based representations explaining heterogeneity in major depressive disorder - Qi Liu; Xinqi Zhou; Chunmei Lan; Xiaolei Xu; Yuanshu Chen; Taolin Chen; Jinhui Wang; Bo Zhou; Dezhong Yao; Keith M. Kendrick; Benjamin Becker; Weihua Zhao (Translational Psychiatry)
Abstract Major depressive disorder (MDD) is a devastating mental disorder characterized by considerable clinical and biological heterogeneity. While comparable clinical symptoms may represent a common pathological endpoint, it is conceivable that distinct neurophysiological mechanisms underlie their manifestation. In this study, both static and model-based dynamic functional connectivity were employed as predictive variables in the normative model to map multilevel functional developmental trajectories and determined clusters of distinguishable MDD subgroups in a large multi-site resting fMRI dataset of 2428 participants (healthy controls: N = 1128; MDD: N = 1300). An independent cohort of 72 participants (healthy controls: N = 35; MDD: N = 37) with both resting fMRI and task-based fMRI data was utilized to validate the identified MDD subtypes and explore subtype-specific task-based neural representations. Our findings indicated brain-wide, interpatient heterogeneous multilevel brain functional deviations in MDD. We identified two distinct and reproducible MDD subtypes, exhibiting comparable severity of clinical symptoms but opposing patterns of multilevel functional deviations. Specifically, MDD subtype 1 displayed positive deviations in the frontoparietal and default mode networks, coupled with negative deviations in the occipital and sensorimotor networks. Conversely, MDD subtype 2 exhibited a significantly contrasting deviation pattern. Additionally, we found that these two identified MDD subtypes exhibited different neural representations during empathic processing, while the subtypes did not differ during implicit face processing. These findings underscore the neurobiological complexity of MDD and highlights the need for a multifaceted approach to diagnosis and treatment that can be tailored specifically to individual subtypes, facilitating personalized and more effective interventions for individuals with MDD.